2017
DOI: 10.1248/bpb.b16-00908
|View full text |Cite
|
Sign up to set email alerts
|

<i>Artesunate</i> Suppresses the Growth of Prostatic Cancer Cells through Inhibiting Androgen Receptor

Abstract: Prostatic cancer (PCa) is a leading cause of cancer related death in males and is often regarded as a kind of androgen-sensitive cancer. Artesunate (ART), a semi-synthetic derivative of the Chinese herb Artemisia annua, is such an anti-cancer agent. However, the effects and mechanism of ART on PCa cells remains unclear. The study aims to elaborate the mechanism of the involvement of androgen receptor (AR) in antiprostatic cancer (PCa) of artesunate (ART). PCa cells 22rvl were used in vivo and in vitro, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…As one of the artemisinin derivatives, DHA was used for malaria treatment in the past decades [13,14]. Recent studies showed that DHA represent as a novel and promising drug for cancer therapy exerts anticancer activity in various cancer cells [15][16][17][18][19][20][36][37][38]. In this study, we confirm the antitumor effect of DHA on BCa.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…As one of the artemisinin derivatives, DHA was used for malaria treatment in the past decades [13,14]. Recent studies showed that DHA represent as a novel and promising drug for cancer therapy exerts anticancer activity in various cancer cells [15][16][17][18][19][20][36][37][38]. In this study, we confirm the antitumor effect of DHA on BCa.…”
Section: Discussionsupporting
confidence: 75%
“…Dihydroartemisinin (DHA) is the primary active products of artemisinin and its derivatives [13], which has been used for malaria treatment for many years [14]. Recent studies have shown that artemisinin and its derivatives such as DHA exhibited anti-tumor activity in many kinds of tumors, such as ovarian cancer, lung cancer, breast cancer, and prostate cancer [15][16][17][18][19]. Mechanistically, DHA suppresses cell proliferation, migration and invasion, as well as induces cell apoptosis [20].…”
Section: Introductionmentioning
confidence: 99%
“…In 1996, Efferth et al ( 4 ) discovered for the first time that ART was able to induce tumor cell apoptosis. Currently, the potential anticancer effects of ART have been reported in numerous tumors, including myelodysplastic syndrome ( 5 , 6 ), multiple myeloma ( 7 ), chronic myeloid leukemia ( 8 ), Burkitt’s lymphoma ( 9 ), bladder cancer ( 10 ), renal carcinoma ( 11 ), cervical ( 12 ), breast ( 13 ), prostate ( 14 ), and head and neck ( 15 ) cancer, hepatocellular carcinoma ( 16 ), esophageal cancer ( 17 ) and CRC ( 18 ). However, the specific mechanism of its antitumor activity remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed mechanism of action for its treatment involves the cleavage of endoperoxide bridges by iron, producing free radicals which damage biological macromolecules, causing oxidative stress in the cells of the parasite (15). Several published case reports and pilot phase I/II trials indicate clinical anticancer activity of this compound in a variety of solid tumors, such as Kaposi's sarcoma, non-small cell lung cancer (NSCLC), and colon, melanoma, breast, ovarian, prostate and renal cancers (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Cases of hepatotoxicity were found when artemisinin was combined with other drugs (29).…”
Section: Artesunate (Art)mentioning
confidence: 99%